If coronavirus disrupts staple crop production the impact on food security could be grave - Chen, Kevin Z. (2020)
The novel coronavirus pneumonia (Covid-19) outbreak that began in Wuhan, in Hubei province, China has quickly spread to at least 75 other countries, causing more than 3,000 deaths.